Relationship between body image and length of exercise with depression in obese people - Hamid, Harlina (Pusat Publikasi Nusantara, 2022)
The aim of this research was to know the relationship between body image and the length of exercise with depression in obese person. Beside both predictors, this research also intended to know the relationship between gender and age with depression in obese person, although both variables of this research taken a position as moderator variables. Subjects were members of two fitness centres in Daerah Istimewa Yogyakarta. They were The Puspita fitness centre dan Lembah Fitness centre. Total subjects were 60. The instruments used in this research were Beck Depression Inventory, Body Image Scale and data of personal identity. Research data were analysed by using regression analysis technique. The result of regression analysis indicated that there was a negative correlation between body image and the length of exercise with depression in obese person. It means that the higher body image of the subject the lower depression they experienced (rpar-xy=-0,359;p<0,01 ); the longer of exercise, the lower depression they experienced( rpar-xy =-0,536;p<0,01); there was a positif correlation between gender and depression in obese person, women more depressive than men (rparxy= 0,270;p<0,05) Their age were not correlated with depression (rpar-xy=- 0,112;p>0,05)